2018
DOI: 10.1021/acs.jproteome.7b00915
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of Zebrafish Heart Regeneration Using an HPLC–ESI–MS/MS Approach

Abstract: Failure to properly repair damaged due to myocardial infarction is a major cause of heart failure. In contrast with adult mammals, zebrafish hearts show remarkable regenerative capabilities after substantial damage. To characterize protein dynamics during heart regeneration, we employed an HPLC-ESI-MS/MS (mass spectrometry) approach. Myocardium tissues were taken from sham-operated fish and ventricle-resected sample at three different time points (2, 7, and 14 days); dynamics of protein expression were analyze… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 44 publications
1
18
0
Order By: Relevance
“…Accordingly, recent studies explored the potential of different approaches capable of stimulating cardiomyogenesis from mature CMs. For example, Ma et al [64] performed in-depth investigation of protein dynamics during heart regeneration of zebrafish using mass spectrometry. In comparison, Tahara et al [65] studied the potential effects of paracrine signals of epicardial and endocardial cells on cardiomyocyte proliferation in zebrafish, whereas Foglia and Poss [61] along with Galdos et al [66] attempted to approach the problem using heart development as a model.…”
Section: Innate Heart Regenerationmentioning
confidence: 99%
See 1 more Smart Citation
“…Accordingly, recent studies explored the potential of different approaches capable of stimulating cardiomyogenesis from mature CMs. For example, Ma et al [64] performed in-depth investigation of protein dynamics during heart regeneration of zebrafish using mass spectrometry. In comparison, Tahara et al [65] studied the potential effects of paracrine signals of epicardial and endocardial cells on cardiomyocyte proliferation in zebrafish, whereas Foglia and Poss [61] along with Galdos et al [66] attempted to approach the problem using heart development as a model.…”
Section: Innate Heart Regenerationmentioning
confidence: 99%
“…For example, it was established that a link exists between the lack of telomerase activity and concomitant telomere dysfunction, which serve as natural barriers to cardiomyocyte proliferation and cardiac regeneration [67]. In addition, p53 signalling was inhibited during heart regeneration [64]. Furthermore, it was shown that the regeneration of damaged myocardium is mediated only by CMs that are adjacent to the injury area [63] whereas inflammation [68] and ROS promote regeneration [69].…”
Section: Innate Heart Regenerationmentioning
confidence: 99%
“…Though an absolute function of cellular vaults has not been determined, several reports suggested these ribonucleoprotein particles might play a role in organ regeneration of zebrafish. Expression analysis revealed after injury, expression of MVP is induced in heart, caudal fin and spinal cord of zebrafish (Ma et al, 2018;Pan et al, 2013;Yoshinari et al, 2009). By using an morpholino-based knock-down approach, researchers observed reduced axonal regrowth after spinal cord transection and proposed MVP supports locomotor recovery and axonal regrowth in adult zebrafish (Pan et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…The heart of zebrafish, for example, was found to regenerate after serious injury, [7,8] due to the specificity of the myocardium environment and proliferative cardiomyocytes. [9] Additionally, neonatal mice cardiomyocytes were found to regenerate mainly through pre-existing cardiomyocytes. [4] Scientists now believe that the human heart is capable of some level of regeneration with varying degrees of myocardium renewal.…”
Section: Introductionmentioning
confidence: 99%